Co3O4-CuNi/reduced graphene composite for non-enzymatic detection of ascorbic acid. (19th September 2019) - Du, Jiawen; Tao, Yiyang; Zhang, Jie; Xiong, Zhichen; Xie, Aijuan; Luo, Shiping; Li, Xiazhang; Yao, Chao
ABSTRACT: A novel Co3 O4 -CuNi/graphene (Co3 O4 -CuNi/RGO) composite was developed by two-step hydrothermal method and used as non-enzymatic electrochemical sensor for ascorbic acid (AA) detection. A series of electrochemical detections declared that Co3 O4 -CuNi/RGO-modified glassy carbon electrode (GCE) has good electrocatalytic activity against AA oxidation, and the optimised sensor has low detection limit (0.34 μM), excellent stability, repeatability and selectivity. In the concentration range of 10-100 μM, the response current of the as-fabricated Co3 O4 -CuNi/RGO AA sensor is proportional to the AA concentration, and the linear equation can be denoted as I pa (mA) = 1.006 + 0.378C (μM), the correlation coefficient R 2  = 0.9917. Moreover, as compared to other reported electrodes, Co3 O4 -CuNi/RGO-modified GCE exhibited a comparable detection limit and provided a simple, easy, low-cost, and non-enzymatic method for AA detection. This highly sensitive Co3 O4 -CuNi/RGO can be further expanded to detect AA in vitamin C tablets, orange, vitamin water and other real samples.